PENGARUH OBJEKTIVITAS, KOMPLEKSITAS TUGAS, RISIKO AUDIT, DAN PROFESIONAL TERHADAP KUALITAS AUDIT - CANDRA WICAKSONO, DHENIES; NYOMAN ALIT TRIANI, NI (Jurnal Akuntansi AKUNESA, 2018)
This research was conducted with the intention of knowing the effect of objectivity, task complexity, audit risk and professional to audit quality. The attitude of the auditor working in a public accounting firm is the object of research in this case. I chose a questionnaire for data collection. Purposive sampling is suitable for determining sample criteria and the criteria is auditors who serve as supervisors and partners in Public Accountant Firm. The research was conducted with a quantitative approach. Data analysis used a Structural Equation Model approach based on Partial Least Square. Final result of the research conducted by the authors indicate that objectivity, task complexity, audit risk and professionals have a positive and significant effect toward audit quality.Keywords: Audit Quality, Objectivity, Task Complexity, Audit Risk, Professional.